The Moderation of Audit Committee and Integrated Enviromental, Social and Governance Disclosure, Financial Reporting Quality, and Firm Value - Prasetiyo, Yudhi (JAS (Jurnal Akuntansi Syariah), 2025)
Purpose – The purpose of this study is to analyze the relationship between ESG (Environmental, Social, and Governance) disclosure, financial reporting quality, and firm valuation, while also investigating the moderating role of the audit committee. Method – The study adopts a mixed method approach, integrating both quantitative and qualitative methods. Data were collected from annual financial reports of publicly listed firms over a three year period, analyzed using logistic regression. Additionally, qualitative data were gathered through interviews with financial expert to validate the quantitative findings and provide deeper insights into governance practices. Findings – The results reveal that ESG disclosure alone does not significantly impact firm valuation. However, investment efficiency plays a crucial role in determining market valuation. The presence of an audit committee strengthens financial reporting quality, demonstrating its moderating effect on ESG disclosure and firm value. These findings are contextualized within the theoretical framework, highlighting key implications, relationships, and potential discrepancies. Implications – This study provides practical and theoretical insights into corporate governance, particularly regarding the role of audit committees in mitigating valuation risks. The findings offer recommendations for policymakers, corporate executives, and investors on enhancing governance structures to improve financial transparency and market stability.